Prognostic value of platelet-to-lymphocyte ratio in hepatocellular carcinoma patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Qingtian Zhou; Zewen Jiang; Tingting Ye; Li Yu; Qinglian Wang; Pin Lin; Yanfeng Shao (BMC Gastroenterology)
Abstract Background The prognostic significance of the Platelet–to–Lymphocyte Ratio (PLR) in patients with hepatocellular carcinoma (HCC) undergoing treatment with immune checkpoint inhibitors (ICIs) remains uncertain. A systematic review and meta–analysis was conducted to assess the prognostic value of PLR in HCC patients receiving ICIs. Methods Potential eligible studies that explored the role of pretreatment PLR in HCC patients received ICIs treatment were retrieved using PubMed, Embase, and the Cochrane Library databases up to March 31, 2024. The Newcastle–Ottawa Scale was used to assess the study quality. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were utilized to investigate the correlation between PLR and both overall survival (OS) and progression–free survival (PFS). Subgroup analysis along with assessments for publication bias and sensitivity were performed to identify any sources of heterogeneity and to confirm the reliability of the pooled outcomes. Results A total of 15 studies were analyzed, with the aggregate findings showing that elevated PLR levels were associated with poorer OS (HR: 1.79, 95%CI: 1.44–2.22, P < 0.001) and PFS (HR: 1.80, 95%CI: 1.40–2.30, P < 0.001) in HCC patients treated with ICIs. Moreover, the subgroup analyses did not alter the direction of results for OS and PFS. Publication bias and sensitivity analysis revealed that there was no significant publication bias among the articles and the pooled results were robust. Conclusion These results show that elevated PLR is related to worse survival in patients with HCC treated with ICIs. PLR may therefore represent an effective indicator of prognosis in HCC undergoing ICIs treatment. Trial registration This study is registered with the International Platform of Registered Systematic Review and Meta–analysis Protocols (INPLASY202450079).